Structural and functional features of reparative osteogenesis under the influence of natural healing factors - Pavlenko, K. V.; Nasibullin, B. A.; Uvarova, Ye. B.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2015)
Pavlenko K. V., Nasibullin B. A., Uvarova Ye. B., Gozhenko A. I. Структурно-функциональные особенности репаративного остеогенеза под влиянием природных лечебных факторов = Structural and functional features of reparative osteogenesis under the influence of natural healing factors. Journal of Education, Health and Sport. 2015;5(3):279-288. ISSN 2391-8306. DOI: 10.5281/zenodo.16453 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A279-288 https://pbn.nauka.gov.pl/works/551960 http://dx.doi.org/10.5281/zenodo.16453 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. УДК 616.718.6-001.5-085.814.5 Структурно-функциональные особенности репаративного остеогенеза под влиянием природных лечебных факторов Structural and functional features of reparative osteogenesis under the influence of natural healing factors К.В. Павленко, Б.А. Насибуллин, Е.Б. Уварова, А.И. Гоженко K.V. Pavlenko, B.A. Nasibullin, Ye.B. Uvarova, A.I.Gozhenko Городская клиническая больница № 11, Одесса Украинский НИИ медицины транспорта, Одесса Городская клиническая больница № 1, Одесса City Clinical Hospital № 11, Odessa Ukrainian Research Institute for Medicine of Transport, Odessa City Clinical Hospital № 1, Odessa Article On 92 white rats - male outbred breeding studied the effect on the healing process of fracture of fibula, as well as ion exchange Ca²+, phosphorus, and alkaline phosphatase activity in blood plasma. The process of fracture healing was similar to the interim indices in rats groups II and III, which was introduced at the fracture site platelet-rich plasma and performed phonophoresis with a fixed dose of poison. By the nature of the formation of callus, they differed. Therefore, in groups I and III process occurred on osteogenic type, and in group II on chondrogenic. In applying the platelet-rich plasma activated alkaline phosphatase decreased plasma calcium and phosphorus content in it. Under the influence of the activation proceeds phonophoresisCa²+ in the fracture, but unlike the II-group, this process is punctuated character. Suggested that the enriched plasma and phonophoresis with "Apizartron" promotes greater intake of calcium in the fracture, and promotes the activation of repair processes in the population of osteocytes. Keywords: fracture of the fibula; platelet-rich plasma; calcium metabolism; alkaline phosphatase; phonophoresis. Реферат На 92 белых крысах – самцах аутобредного разведения изучали влияние на процесс заживления перелома малой берцовой кости, а также обмен ионов Са²+, фосфора и активность щелочной фосфатазы в плазме крови. Процесс заживления перелома был одинаков по временным показателям у крыс II и III групп, которым в месте перелома вводилась плазма обогащенная тромбоцитами и проводился фонофорез с фиксированной дозой яда. По характеру процесса образования костной мозоли они отличались. Так в I и III группах процесс происходил по остеогенному типу, а во II группе по хондрогенному. При применении плазмы обогащенной тромбоцитами активируется щелочная фосфатаза плазмы и снижается содержание фосфора и кальция в ней. Под влиянием фонофареза происходит активация поступления Са²+ в облисть перелома, но в отличие от II-группы этот процесс носит перемежающий характер. Высказано пердположение, что обогащенная плазма и фонофарез с «Апизартноном» способствует более активному поступлению кальция в область перелома, а также способствует активации процессов репарации в популяции остеоцитов. Ключевые слова: перелом малоберцовой кости; плазма обогащенная тромбоцитами; обмен кальция; щелочная фосфатаза; фонофарез.